The impact of selected food additives on the gastrointestinal tract in the example of nonspecific inflammatory bowel diseases - Sara Jarmakiewicz - Czaja; Dominika Piątek; Rafał Filip (Archives of Medical Science, 2021)
Various types of food additives are widely used in the food industry. Due to their properties extending the usefulness for consuming food products, they give them different colours, consistency, or taste. The products are marked ‘E’ and the code is assigned to the subscription used. Many of the supplements affect human health negatively. Emulsifiers or stabilizers can lead to epithelial loads and the development of inflammation. Sucrose and other sweeteners may change the composition of the intestinal microflora and thus lead to intestinal blockage. Some additives classified as preservatives are available and may predispose to intestinal dysbiosis. Available substances belonging to food dyes may predispose to genotoxic and cytotoxic effects and cause inflammation in the intestines. Substances added to food can also cause disorders of intestinal homeostasis.